2003
DOI: 10.1021/jp0225469
|View full text |Cite
|
Sign up to set email alerts
|

Wave Packet Study of Ultrafast Relaxation in Ice Ih and Liquid Water. Resonant Intermolecular Vibrational Energy Transfer

Abstract: By using quantum chemistry, the fundamental normal modes and the frequencies of ice Ih and room-temperature water clusters containing up to 15 water molecules are constructed. These normal modes are then used on the basis of assumed harmonic dynamics for analyzing the survival probability and energy decay of wave packets which reflect symmetric and asymmetric stretch excitations in single water molecules. Following symmetric stretch excitation, it is found that the wave packet survival probability and the OH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…Such VET has already been observed by Woutersen and Bakker. 23 Poulsen et al 24 simulated VET in pure water, and found a time transfer from 80 to 250 fs, in very good agreement with our data. This allows us to depict the model of diffusion in pure water as follows: the pump pulse, via libration modes, excites OH vibrator at a given frequency.…”
Section: Model and Discussionsupporting
confidence: 90%
“…Such VET has already been observed by Woutersen and Bakker. 23 Poulsen et al 24 simulated VET in pure water, and found a time transfer from 80 to 250 fs, in very good agreement with our data. This allows us to depict the model of diffusion in pure water as follows: the pump pulse, via libration modes, excites OH vibrator at a given frequency.…”
Section: Model and Discussionsupporting
confidence: 90%
“…5 Alter-natively, intermolecular ET was studied by using harmonic approximations. 8,9 In this work, we use numerical integration of the Schrödinger equation 10 ͑NISE͒ in a fully anharmonic nonadiabatic simulation procedure, explicitly treating the intermolecular coupling, as well as fluctuations and anharmonicities of transition frequencies and dipole moments, to calculate the 2DIR-PE and pump probe ͑PP͒ response of OH stretch vibrations in liquid water. With this new procedure, we find excellent agreement with the recent experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…As a result the fastest dynamics of water (500 nm thickness) at room temperature has now been determined with 70 fs time resolution. These recent experimental results on neat water emphasize the necessity of theoretical studies on the determination of the couplings of librational modes with the O−H stretching oscillator [194], as well as intermolecular resonant vibrational energy transfer [195,196], fluctuations of the hydrogen bond network of neat water [176,197], and reorientational dynamics [198]. 7.9).…”
Section: Coherent Response Of Neat Liquid Watermentioning
confidence: 93%